Respond to this Question
Similar Questions

math
Evaluate. 1. sin^1(1/2) 2. cos^1[(root 3)/2] 3. arctan[(root3)/3] 4. cos(arccos2/3) 5. arcsin(sin 2pi) 6. sin(arccos 1)
asked by anonymous on January 7, 2010 
Trigonometry
I need help with I just can't seem to get anywhere. this is as far as I have got: Solve for b arcsin(b)+ 2arctan(b)=pi arcsin(b)=pi2arctan(b) b=sin(pi2arctan(b)) Sub in Sin difference identity let 2U=(2arctan(b))
asked by Jen on July 27, 2007 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x +
asked by hayden on February 23, 2009 
Trigonometry
Evaluate please: a.) arcsin(sin 13pi/16) b.) arccos(cos[pi/18]) c.) arcsin(sin pi/18 d.) arcsec(√2) e.) arctan(√3/3)
asked by Liv on November 26, 2016 
math
Eliminate the parameter (What does that mean?) and write a rectangular equation for (could it be [t^2 + 3][2t]?) x= t^2 + 3 y = 2t Without a calculator (how can I do that?), determine the exact value of each expression. cos(Sin^1
asked by Anonymous on August 3, 2007 
maths
Please can you help me with this question? Choose the option which is a false statement: A arctan(tan2/3pi))=1/3pi B arccos(cos(3/4pi))=3/4pi C sin(arcsin(1/2pi))=1/2pi D arcsin(1/2squareroot3)=1/3pi E arcsin(sin(3/4pi))=1/4pi
asked by janet on May 26, 2011 
tigonometry
expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by b and using that cos(b)= cos(b) sin(b)= sin(b) gives: sin(ab) = sin(a)cos(b)  cos(a)sin(b)
asked by Pablo on November 26, 2006 
calculus
Differentiate. y= (cos x)^x u= cos x du= sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x1) * (sin x) =  x sin(x)cos^(x1)(x)
asked by Chelsea on March 10, 2011 
Calc.
Differentiate. y= (cos x)^x u= cos x du= sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x1) * (sin x) =  x sin(x)cos^(x1)(x)
asked by Chelsea on March 9, 2011 
algebra
Can someone please help me do this problem? That would be great! Simplify the expression: sin theta + cos theta * cot theta I'll use A for theta. Cot A = sin A / cos A Therefore: sin A + (cos A * sin A / cos A) = sin A + sin A = 2
asked by Valerie on February 18, 2007